A view from Family Law and Inheritance Law, concerning the right of residence of the surviving spouse or survivor is the case of the cohabitation - Aguilar Llanos, Benjamín (2015)
This article focuses on the family estate and the natural fact as death does not end the legal relationships that have led to the heritage that formed the family heritage, this transcends the subject. Therefore, the law regulates the transfer of the rights goods and obligations of the deceased in favor of the person that are his successors. In conclusion, death generates legal consequences.